Elicitation Techniques in Turn-taking Practices in EFL Classroom Interaction - Desfiyenti; Indah Rahmalia; Ridianto (Pustaka Galeri Mandiri, 2022)
This research aimed to analyze the practice of elicitation technique in EFL classroom interaction. The research was conducted in descriptive qualitative method. There were three English teachers taken as participant. The data were collected by observation. The data analysis was followed by Gay (2010). The result of this research revealed eight types of elicitation; elicit: inform, elicit: confirm, elicit: product, elicit: choice, elicit: repeat, elicit: process, elicit: clarify, and elicit: agree were used by English teachers. Elicit: inform was the most frequent type of elicitation used which reached 58,30 %. This indicates that English teachers had applied elicitation techniques in turn-taking practices in EFL classroom interaction.